Effect of Aqueous Extract of Ginger (Zingiber officinale) on Blood Biochemistry Parameters of Broiler - Saeid, Jamel M.; Mohamed , Arkan B.; AL-Baddy, Maad A. (International Journal of Poultry Science, 2010)
This study was carried out at the Poultry of Animal Resource, College of Agriculture, University of Tikrit. The present study was conducted to explore the usage of different levels of aqueous extract of ginger at concentration of 0.4 and 0.6% respectively supplemented to drinking water on the Physiological Performance and Lipid Profile of the Broiler Chickens. One hundred and eighty of 3 weeks old broiler chicks (ROSS) raised to 6 weeks of age. The birds were distributed into 3 treatment groups with three replicates per treatment (20 birds per treatment). Aqueous extract of ginger was the rate 0.4 and 0.6% with water offered to treatments T2 and T3 respectively while treatment one served as control. The result of the physiological parameter showed significant difference between treatments. However glucose and uric acid level showed a significant differences (p<0.05) between T2 (0.4% ginger extract) and T3 (0.6% ginger extract) and control. The total protein, Albumin and Globulin were not differ significantly between the treatment groups. Serum HDL-cholesterol, LDL-cholesterol and VLDL-cholesterol level revealed no significant (p>0.05) difference between treatments but serum cholesterol level was a significantly lower in the 0.4 and 0.6% aqueous extract of ginger (p<0.05) than control. Findings of the research study indicated that groups receiving ginger infusion at the rate 0.4 and 0.6% of drinking water showed better physiological performance and lipid profiles in broiler.